Characteristics and Outcomes in Patients with Venous Thromboembolism Taking Concomitant Anti-Platelet Agents and Anticoagulants in the AMPLIFY Trial - Cohen, Alexander T.; Agnelli, Giancarlo; Buller, Harry R.; Gallus, Alexander; Raskob, Gary E.; Sanders, Paul; Thompson, John; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2019)
The double-blind, randomized, AMPLIFY trial compared 6 months' treatment with apixaban (10 mg twice daily for 7 days and 5 mg twice daily thereafter) versus conventional treatment (subcutaneous enoxaparin [1 mg/kg twice daily for ≥ 5 days] overlapped and followed by warfarin [international normalized ratio = 2.0–3.0]) in patients with acute venous thromboembolism (VTE). This post hoc analysis of AMPLIFY compared outcomes among those taking or not taking concomitant anti-platelet therapy. The primary efficacy outcome was recurrent VTE or VTE-related death; the principal safety outcome was major bleeding. Of 5,365 (apixaban, n = 2,676; enoxaparin/warfarin, n = 2,689) randomized patients, 813 (apixaban, n = 402 [15%]; enoxaparin/warfarin, n = 411 [15%]) took concomitant anti-platelet therapy, of which 92% consisted of low-dose aspirin. Rates of VTE or VTE-related death were similar whether or not anti-platelet agents were taken (apixaban: 3.6 and 2.0%; enoxaparin/warfarin: 3.0 and 2.6%; anti-platelet use: relative risk [RR], 1.23; 95% confidence interval [CI], 0.58–2.62; no anti-platelet use: RR, 0.77; 95% CI, 0.52–1.13); interaction p-value = 0.299. Major bleeding rates were threefold higher in those taking versus those not taking anti-platelet agents (apixaban: 1.2 and 0.4%; enoxaparin/warfarin: 4.1 and 1.4%; anti-platelet use: RR, 0.30; 95% CI, 0.11–0.81; no anti-platelet use: RR, 0.31; 95% CI, 0.15–0.63); interaction p-value = 0.924. Concomitant anti-platelet therapy produced a proportionally similar increase in major bleeding in patients randomized to apixaban or conventional therapy, but there were fewer major bleeds with apixaban. Therefore, the overall safety of apixaban over conventional therapy was maintained in patients receiving anti-platelet therapy. Clinicaltrials.gov: NCT00643201.
Keywords: anti-platelet agents; venous thrombosis; clinical trials: oral anticoagulants; deep vein thrombosis; pulmonary embolism